2020
DOI: 10.3389/fimmu.2020.01377
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide-Based PD1 Antagonist Enhances T-Cell Priming and Efficacy of a Prophylactic Malaria Vaccine and Promotes Survival in a Lethal Malaria Model

Abstract: The blockade of programmed cell death-1 (PD1) and its ligand PDL1 has been proven to be a successful immunotherapy against several cancers. Similar to cancer, PD1 contributes to the establishment of several chronic infectious diseases, including malaria. While monoclonal antibodies (mAbs) targeting checkpoint receptors are revolutionary in cancer treatment, the immune-related adverse events (irAEs) may prevent their utilization in prophylactic and therapeutic treatments of infectious diseases. The irAEs are, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Furthermore, peptide-based immunomodulators offer more formulation and delivery options, and have better tissue penetration and rapid synthetic manufacturing (31)(32)(33)(34). We recently reported that LD01, a 22-amino acid peptide derived from a Bacillus bacteria, antagonized PD-1, enhanced antigen-specific CD8 T-cell expansion, and promoted the survival of mice in a lethal malaria model (35).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, peptide-based immunomodulators offer more formulation and delivery options, and have better tissue penetration and rapid synthetic manufacturing (31)(32)(33)(34). We recently reported that LD01, a 22-amino acid peptide derived from a Bacillus bacteria, antagonized PD-1, enhanced antigen-specific CD8 T-cell expansion, and promoted the survival of mice in a lethal malaria model (35).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have recently demonstrated that when a peptide-based PD1 antagonist is prophylactically-combined with an adenovirus-based or irradiated sporozoitebased malaria vaccination, antigen-specific CD8 T cell expansion is enhanced (48). Additionally, with the same peptide-based PD1 antagonist, we found that therapeutic treatment of mice infected with a lethal malaria strain resulted in survival that was associated with lower numbers of Treg cells (48). When taken together with the data suggesting poor immune response to malaria infection is partially due to Treg cell activation and that interference in regulation of immune checkpoint proteins can lead to chronic malaria disease (24)(25)(26), we posit the need for minimizing epitopes cross-conserved with the human proteome and the inclusion of mechanisms to boost immune response through modulation of checkpoint proteins such as PD1 in best practice PfCSP vaccine development strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Further, as programmed cell death (PD1) expression in Treg cells is indispensable for their suppressive functions ( 46 ) and PD1 upregulation upon naïve T cell activation plays a regulatory role in naïve-to-effector T cell differentiation ( 47 ), modulation of PD1 signaling may increase vaccine induced, antigen-specific responses. In this regard, we have recently demonstrated that when a peptide-based PD1 antagonist is prophylactically-combined with an adenovirus-based or irradiated sporozoite-based malaria vaccination, antigen-specific CD8 T cell expansion is enhanced ( 48 ). Additionally, with the same peptide-based PD1 antagonist, we found that therapeutic treatment of mice infected with a lethal malaria strain resulted in survival that was associated with lower numbers of Treg cells ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we report on LD10, an active, 18-amino acid derivative of our previously reported peptide ( Phares et al, 2020 ). In vitro , LD10 demonstrated greater potency at impairing PD-1 receptor signaling relative to LD01.…”
Section: Introductionmentioning
confidence: 92%
“…In non-human primates, immunization with an SIV Gag adenovirus-based vaccine in combination with an anti-PD-1 monoclonal antibody (mAb) significantly elevated peak Gag-specific T cell responses ( Finnefrock et al, 2009 ). Further, we recently showed that antagonizing the PD-1 receptor during prophylactic immunization with an adenovirus-based or radiation-attenuated sporozoite-based malaria vaccine significantly enhanced the number of antigen-specific CD8 + T cells ( Kotraiah et al, 2020 ; Phares et al, 2020 ). These observations suggest that PD-1 modulation may be a critical T cell-focused immunomodulator capable of enhancing T cell expansion and differentiation, resulting in increased numbers and functionality of effector and memory T cells.…”
Section: Introductionmentioning
confidence: 99%